Tourism as a transformation and leisure tool - Alvim Côrtes, Lucília (Argumentos - Revista do Departamento de Ciências Sociais da Unimontes, 2023)
The present study observes the relevance of intercultural processes present in the touristic activity and tourism’s multidisciplinary role as a source of leisure, culture, and welfare. The aim of this work is to demonstrate tourism’s educational role and the relevance of touristic activity as a transformative leisure tool that can contribute to the development of intercultural competences. This study not only assesses the development of competences in specific tourist groups but also the positive and negative impacts to the populations involved in the touristic activity. Through applying education indicators to the field of tourism, where the impacts of touristic activities with educational purposes on the development of competences in those who directly or indirectly participate of said activities have been analysed, the present study sheds light on a formative and mobilizing potential of the leisure activities in general. It is a fundamental intensive qualitative research, with quantitative data complementation and mixed technique of data collection, given the age and sociodemographic diversities of the target group. The study’s results confirm the relevance of the touristic activities’ impacts on the most diverse sections of society and on a global scale.